2015
DOI: 10.5755/j01.ms.21.4.9563
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plastic Deformation and Nanocrystallization Mechanism of Welded Joint of 16MnR Steel Treated by Ultrasonic Impact

et al.

Abstract: The welded joint surfaces of 16MnR steel were treated using an ultrasonic impact machine. The effects of ultrasonic impact treating (UIT) on the plastic deformation and nanocrystallization mechanism of the welded joints of 16MnR steel were studied. The micro-structural features of the surface layer produced by UIT were observed by scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM), and micro-hardness measurements were performed. Experimental results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…At the initial stage of ultrasonic peening treatment, the plastic deformation in the material first occurs in some grains whose orientation is easy to slip, but due to the obstruction of grain boundaries, the plastic deformation of grains in the same layer is uneven, and the plastic deformation gradually extends from the surface layer of the material to the deep layer of the material, so the microstructure presents a gradient distribution along the thickness direction [3]. After ultrasonic peening treatment, the geometric shape of the welding toe has changed, and the discontinuity of the geometric shape of the welding toe has changed into a smooth transition, and the original micro-bumps, grooves, and other surfaces have disappeared, as shown in Figures 2 and 3.…”
Section: Macro-morphology Of Welding Toementioning
confidence: 99%
“…At the initial stage of ultrasonic peening treatment, the plastic deformation in the material first occurs in some grains whose orientation is easy to slip, but due to the obstruction of grain boundaries, the plastic deformation of grains in the same layer is uneven, and the plastic deformation gradually extends from the surface layer of the material to the deep layer of the material, so the microstructure presents a gradient distribution along the thickness direction [3]. After ultrasonic peening treatment, the geometric shape of the welding toe has changed, and the discontinuity of the geometric shape of the welding toe has changed into a smooth transition, and the original micro-bumps, grooves, and other surfaces have disappeared, as shown in Figures 2 and 3.…”
Section: Macro-morphology Of Welding Toementioning
confidence: 99%
“…UIT processing is very similar to traditional ultrasonic shot peening but instead of using impact balls, it uses a hemispherical impact needle(s) applied directly to the target materials at a high frequency of more than 20 kHz, so that the substrate is subjected to severe plastic deformation on its surface. Under the repeated high-frequency, high-energy impact of the impact needle(s), sustainably formed severe regional plastic deformation, surface microstructure evolution, and residual compressive stress are introduced in the treated region of the substrate [29,30]. In this case, the desired residual compression stress and deformation can be achieved through adjusting the impact parameters [31].…”
Section: Introductionmentioning
confidence: 99%
“…Up until now, owing to its efficiency, low cost, and minimum geometrical restriction, UIT has been shown to be a very promising technique to use for surface enhancement, and the effects of this on the wear properties of the stainless steel coating have been extensively studied globally. Research on the increased wear resistance of 16MnR steel [30], Ti-6Al-4V alloy [32], 316L stainless steel [24], AZ31B magnesium alloy micro-arc oxidation composite coating [33], and Al0.5CoCrFeMnNi high-entropy alloy coatings [34] induced with UIT has been reported, and many of these studies found that the improvements in wear resistance can be attributed to the following two reasons: the modification of surface topography and the synergistic effects of grain refinement and hardness enhancement. It is more effective to design a coating with a gradient structure in order to achieve excellent tribological properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, surface nanocrystallization techniques such as surface mechanical attrition treatment (SMAT) [9], shot peening (SP) [10], hammer peening [11], laser shock peening (LSP) [12] and ultrasonic impact treatment (UIT) [13] are more attractive and expected to present new ideas to realize materials' nanostructured layer in various surface protection applications.Compared with the other mechanical surface treatment techniques mentioned above, it is demonstrated that the UIT is more convenient and economical and controllable to rapidly realize surface nanocrystallization over a large area [13,14]. Up to now, UIT has been more widely used to eliminate the welding residual stresses [14,15] being improved the microstructure of the near-surface region [16,17] and the fatigue behaviors of welded joints [18,19] through severe plastic deformation. Previous investigations reported that the UIT could generate compressive residual stress and refine the grains on surface layer of welded structures, resulting in the enhanced mechanical properties.…”
mentioning
confidence: 99%